2019
DOI: 10.1186/s12974-019-1663-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of amyloid precursor protein exacerbates early inflammation in Niemann-Pick disease type C

Abstract: BackgroundNiemann-Pick disease type C (NPC) is a progressive neurodegenerative condition that results in early fatality. NPC is inherited in an autosomal recessive pattern from mutations in NPC1 or NPC2 genes. The etiology of NPC is poorly defined. In that regard, neuroinflammation occurs early in the disease and we have recently unveiled an atypical pattern of interferon signaling in pre-symptomatic Npc1−/− mice, with microglial activation, anti-viral response, activation of antigen-presenting cells, and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…IP-10 is a chemokine involved in the attraction of immune cells at inflammation sites [70], and IP-10 levels are frequently elevated during CNS infection [71]. High levels of IP-10 are associated with some LSDs [64,72,73]. Our data and other studies suggest that curcumin suppresses the expression of IP-10 [74,75], which could mean that it may help to reduce inflammation.…”
Section: Ucbct and Curcumin Administrationsupporting
confidence: 56%
See 1 more Smart Citation
“…IP-10 is a chemokine involved in the attraction of immune cells at inflammation sites [70], and IP-10 levels are frequently elevated during CNS infection [71]. High levels of IP-10 are associated with some LSDs [64,72,73]. Our data and other studies suggest that curcumin suppresses the expression of IP-10 [74,75], which could mean that it may help to reduce inflammation.…”
Section: Ucbct and Curcumin Administrationsupporting
confidence: 56%
“…As mentioned earlier, elevated levels of eotaxin correlate with a number of nervous system disorders. To summarize, eotaxin is elevated in the cerebellum of model mice of Niemann-Pick type C (NPC) [64], is negatively correlated with gray matter in patients older than 60 years with late-life major depression [65] and is possibly associated with the loss of dopaminergic neurons in patients with Parkinson's disease [66]. In a mouse model of allergic asthma, it was shown that treatment with curcumin leads to suppression of the expression of many inflammatory cytokines, including eotaxin [67].…”
Section: Ucbct and Curcumin Administrationmentioning
confidence: 99%
“…However, widespread protein and brain tissue degradation is a consistent feature of open skull, severe TBI models per observation of apoptosis (Brophy et al, 2009;Cartagena et al, 2013), as well as axonal fiber and cellular degeneration (Brophy et al, 2009;Shear et al, 2009;Gajavelli et al, 2015). A novel aspect of this model is presented by this study, which found that miRNAs affected by PBBI over time collectively mapped to APP processing, a key feature of neurodegeneration (Roberts et al, 1994;Nguyen, 2019;Shin et al, 2019), that overlaps the timeframe of widespread degradation in this model.…”
Section: Pbbi-induced Mirna Dysregulation Is Associated With Bace1 Upmentioning
confidence: 53%
“…In mice, the outcome of a given mutation varies with the genetic background of strains [37,135,[215][216][217][218]. Numerous double mutant mice have been created to test whether and how specific candidate genes impact the disease [163,173,177,190,191,[219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234][235]. Sex-dependent differences in behavior [236], life span [37,134], and responses to immune activation [237] and to potential therapies [171,238] were reported in some NPC1 mutant mice, raising the question of whether sex is a modifying factor in NPC disease [37] as in other cholesterol-related pathologies [239][240][241][242] and normal cholesterol homeostasis [243,244].…”
Section: Mammalian Modelsmentioning
confidence: 99%